(untitled) (Philological Studies, 2019)
Globalization has brought new way of living and new political and economic conditions. The most important process for Europe is the devotion to the unification of the European Union. When the new members joint the EU, they must implemented a series of reforms in a line with the European laws. Macedonia is a unique example that among needed objections has an additional one - to change its constitutional name for both external and internal use. This condition - a dispute over the name issue - was imposed by the Greek policy with veto on the accession of the Republic of Macedonia into the EU and NATO integrations. The terms of globalization that favor the right to self-determination, the right to respect for the other, the protection of identities, in fact, are specified for the Macedonian people - change the name if you wish to become part of democratic Europe. But, the question remains – is this brings security and prosperity or uncertainty that might entails the change of identity.